2015
DOI: 10.1111/bpa.12239
|View full text |Cite
|
Sign up to set email alerts
|

Pilomyxoid Astrocytoma (PMA) Shows Significant Differences in Gene Expression vs. Pilocytic Astrocytoma (PA) and Variable Tendency Toward Maturation to PA

Abstract: Pilomyxoid astrocytomas (PMAs) manifest a more aggressive clinical course than pilocytic astrocytomas (PAs). Development of effective therapies demands a better biological understanding of PMA. We first conducted gene expression microarray analysis of 9 PMA and 13 PA from infra- and supra-tentorial sites. Unsupervised hierarchical clustering analysis demonstrated that tumors grouped according to anatomic site, not diagnosis. Gene expression profiles were then contrasted between 8 PMAs and 6 PAs, all supratento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…IGF2BP3 mRNA and protein levels are also upregulated in GBMs but not in lower grade astrocytomas [97]. Particularly, IGF2BP3 is one of the genes overexpressed in pilomyxoid astrocytomas (PMAs) compared with a less aggressive pilocytic astrocytomas (PAs), according to a gene expression microarray analysis of 9 PMAs and 13 PAs from infra-and supratentorial sites [98]. A microarray analysis in glioma cells shows that IGF2BP3 mediates regulation of direct targets at transcriptome associated with cell cycle process, whereas direct targets at the translatome participating in apoptosis related pathways [99].…”
Section: Igf2bp Familymentioning
confidence: 99%
“…IGF2BP3 mRNA and protein levels are also upregulated in GBMs but not in lower grade astrocytomas [97]. Particularly, IGF2BP3 is one of the genes overexpressed in pilomyxoid astrocytomas (PMAs) compared with a less aggressive pilocytic astrocytomas (PAs), according to a gene expression microarray analysis of 9 PMAs and 13 PAs from infra-and supratentorial sites [98]. A microarray analysis in glioma cells shows that IGF2BP3 mediates regulation of direct targets at transcriptome associated with cell cycle process, whereas direct targets at the translatome participating in apoptosis related pathways [99].…”
Section: Igf2bp Familymentioning
confidence: 99%
“…Interestingly, a curious phenomenon of “maturation” has been described in a small subset of PMA with recurrent tumors “maturing” into PA-like neoplasms. [ 4 5 6 ] This is more frequently observed in tumors with “intermediate” features between PMA and PA designated as “intermediate pilomyxoid forms”. [ 3 6 ] The novelty in the present case is the presence of dysmorphic ganglion cells in PA in the 1 st resection with recurrent lesions depicting PMA-like features, an observation which is reverse of “maturation”.…”
Section: Discussionmentioning
confidence: 99%
“…However, the recent updated WHO classification has questioned assigning it a higher grade in view of considerable variation in their outcome in different studies. [ 3 ] An interesting and rare phenomenon of “maturation” has been observed with examples of PMA undergoing “maturation” to PA in subsequent recurrences[ 4 5 6 ] which is more commonly observed in the “intermediate” lesions. “Intermediate” lesions are tumor displaying features of typical PMA admixed with areas resembling classic PA.[ 4 ] Herein, we describe a rare example of PA with gangliocytic component showing a rapid regrowth within 1½ years with differentiation to PMA on the third recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…However, PMAs affect infants whose body is still developing, and then PMA cells may also proliferate and develop in such an infantile microenvironment, in addition to tumour genetic alterations. Recently, KleinschmidtDeMasters et al 12 reported interesting information describing the molecular analysis of PMAs, including the difference in developmental gene alterations among PMA, PA and PMA cases showing the tendency towards maturation to PA. For a better understanding of the maturation from PMA to PA, further clinicopathological and genetic analyses using a large number of PMA cases are needed.…”
Section: Discussionmentioning
confidence: 99%